50 Insertable cardiac monitors to detect af in "cryptogenic stroke". (28th September 2016) - Mahon, C; McCreery, C; Noone, I; Flynn, P
Abstract : Background: Ischaemic stroke is a major cause of morbidity and mortality. The aetiology remains undetermined in 20–40% even after costly routine evaluation. This results in a diagnosis of exclusion of cryptogenic stroke. Atrial fibrillation (AF) confers a five-fold risk of ischaemic stroke and one in five of all strokes is attributed to this arrhythmia, undiagnosed silent AF is a likely cause of some cryptogenic strokes. The recent Crystal Trial demonstrated 8.9% detection of AF in the follow up of patients with a prior diagnosis of crytptogenic stroke with an insertable cardiac monitor. The ESC guidelines suggest that consideration should be given to insertion of a cardiac monitor in certain high risk patients presenting with a non- debilitating stroke and in whom a high index of suspicion exists for the presence of silent AF. In Ireland, the annual cost of stroke is estimated to be 489–805 euro million, with direct costs accounting for 2–4% of total health expenditure. Using demographic changes alone, with stroke incidence and prevalence kept constant, annual cost is estimated to increase by 58% from by 2021 to be between 743 and 1266 million euro. Preventative measures do exist including smoking cessation, reducing alcohol consumption, physical inactivity, diabetes and obesity. The reassessment of high risk patients with a previous diagnosis of cryptogenic stroke by confirming silent AF and initiating appropriate oral anti-coagulation may prevent more debilitating future strokes, further reducing the impact on quality of life. Cost benefit analysis have demonstrated the effectiveness of this intervention. Method: This was a single centre prospective study commenced in January 2014 and is currently ongoing. Ethical approval was obtained from the hospital ethics committee. High risk patients with a non debilitating stroke were assessed for suitability for inclusion by the stroke team. Patients were high risk based on the presence of cardiovascular risk factors and a confirmed ischaemic stroke on MR brain imaging. A non-debilitating stroke was defined as Rankin score of less than or equal to 2. All patients had completed the standard work up for ischaemic stroke and carried a diagnosis of cryptogenic stroke. Results: In our single centre prospective experience 52 high risk patients, with a non debilitating ischaemic stroke, were selected for insertable cardiac monitoring to detect silent AF. Twenty patients (40%) were found to have silent AF. The mean age was 72.9 years. The average CHADSVAC score was 6. The mean time to diagnosis of AF was 2.9 months. Appropriate oral anticoagulation was initiated in all patients in whom AF was detected. No patient in this study has had a further stroke event. Conclusion: In this single centre experience our results are in keeping with previous studies that demonstrate that in highly selected patients cardiac monitoring can be utilised to capture silent AF and to initiate appropriate therapy.